2010
DOI: 10.3892/or_00000888
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative serum α-fetoprotein level is a useful predictor of recurrence after hepatectomy for hepatocellular carcinoma

Abstract: Abstract. We evaluated the clinical value of perioperative ·-fetoprotein (AFP) and des-Á-carboxy prothrombin (DCP) levels in predicting recurrence of hepatocellular carcinoma (HCC) after curative resection, with a focus on the time course as surveillance tools. A total of 165 consecutive HCC patients who had undergone curative hepatectomy at our institution from 2005 to 2007 and whose serum AFP and DCP had been measured before and after hepatectomy were included in this study. The minimum postoperative levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[14][15][16] Previous studies have reported that a small percentage of initially AFP-negative patients (3.7%) experienced recurrence if they had a positive serum AFP level following surgery, while no recurrence occurred in patients with a consistently negative AFP level after surgery. 17 Our previous study also demonstrated that changes in postoperative AFP levels, even within the normal range, could predict liver cancer recurrence. 6 Another study suggested that models based on AFP variation after surgery, using intelligent algorithms, could predict recurrence in AFP-negative HCC patients.…”
Section: Discussionmentioning
confidence: 85%
“…[14][15][16] Previous studies have reported that a small percentage of initially AFP-negative patients (3.7%) experienced recurrence if they had a positive serum AFP level following surgery, while no recurrence occurred in patients with a consistently negative AFP level after surgery. 17 Our previous study also demonstrated that changes in postoperative AFP levels, even within the normal range, could predict liver cancer recurrence. 6 Another study suggested that models based on AFP variation after surgery, using intelligent algorithms, could predict recurrence in AFP-negative HCC patients.…”
Section: Discussionmentioning
confidence: 85%
“…Serum AFP-negative patients rarely show fluctuations in serum AFP, even if they relapse after surgery; only 3.7% of patients were found to have serum AFP-positive conversion. 15 Therefore, patients who exhibit serum AFP-negative level lack valuable indicators. The present subgroup analysis of serum AFP-positive or -negative levels in patients showed that the HMR model was more effective than the traditional method (serum AFP level) for detecting recurrence in the former, and for AFP-negative patients, the sensitivity and specificity were >70%.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A previous study showed that when the preoperative AFP was negative (positive), the sensitivity for detection of HCC recurrence was 3.7% (80.0%). 15 In addition, our previous study found that changes in postoperative AFP levels had higher sensitivity than AFP levels within the normal range. 16 Therefore, the predictive ability of serum AFP for postoperative surveillance is hampered by a high rate of false positives.…”
Section: Introductionmentioning
confidence: 92%
“…Tumor markers, as simple and inexpensive indicators, have been widely used in clinical practice. Alpha fetoprotein (AFP), which was discovered in 1963, has become the most important serum marker for diagnose HCC and is also widely used in postoperative recurrence monitoring [6,7] . Unfortunately, the positive rate of AFP expression in HCC is only approximately 70%, [8] and nearly 40% of HCC is AFP-negative [9–11] .…”
Section: Introductionmentioning
confidence: 99%
“…Alpha fetoprotein (AFP), which was discovered in 1963, has become the most important serum marker for diagnose HCC and is also widely used in postoperative recurrence monitoring. [6,7] Unfortunately, the positive rate of AFP expression in HCC is only approximately 70%, [8] and nearly 40% of HCC is AFP-negative. [9][10][11] Due to the elevation of AFP in some active liver diseases, reproductive system tumors and pregnancy, the diagnostic specificity of AFP for HCC is impacted.…”
Section: Introductionmentioning
confidence: 99%